2004
DOI: 10.1002/ar.a.20140
|View full text |Cite
|
Sign up to set email alerts
|

Skeletal muscle development in normal and double‐muscled cattle

Abstract: This study examined the effect of genotype on prenatal muscle development in both normal-muscled (NM) animals and in double-muscled (DM) animals harboring a mutation in the gene for myostatin that results in the production of a functionally inactive protein. The following muscle development parameters were analyzed at four gestational ages: muscle weight, fiber type, by both enzyme histochemistry and myosin heavy-chain (MHC) immunocytochemistry, and average fiber area. The weights of both M. vastus lateralis a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
11
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 34 publications
2
11
0
Order By: Relevance
“…Considering the fetal programming of skeletal muscle development [9], [12], these findings are consistent with generally medium to high heritabilities reported for postnatal myofibre size and muscle mass in mammals, including bovine [18], [19], [24], [50], [51]. Since myotubes are immature myofibres that decrease in size as myogenesis progresses [52], both the predominant contribution of the paternal genome to variation in fast myotube cross sectional area (CSA), and the predominant contribution of the maternal genome to variation in fast myofibre CSA ( Figure 2 ), indicate specific roles of maternal and paternal genomes in myofibre differentiation and maturation.…”
Section: Discussionsupporting
confidence: 85%
“…Considering the fetal programming of skeletal muscle development [9], [12], these findings are consistent with generally medium to high heritabilities reported for postnatal myofibre size and muscle mass in mammals, including bovine [18], [19], [24], [50], [51]. Since myotubes are immature myofibres that decrease in size as myogenesis progresses [52], both the predominant contribution of the paternal genome to variation in fast myotube cross sectional area (CSA), and the predominant contribution of the maternal genome to variation in fast myofibre CSA ( Figure 2 ), indicate specific roles of maternal and paternal genomes in myofibre differentiation and maturation.…”
Section: Discussionsupporting
confidence: 85%
“…On the other hand, Girgenrath et al (2005) showed that MSTN deficiency in mouse caused up-regulation of faster MyHC isoforms and down-regulation of MyHCslow in both fast-(extensor digitorum longus) and slow-type (soleus) muscles. Moreover, percentages of slow-type muscle fibers of the vastus latelaris and vastus medialis muscles of prenatal calves are lower in the DM than in the NM (Martyn et al 2004). Moreover, percentages of slow-type muscle fibers of the vastus latelaris and vastus medialis muscles of prenatal calves are lower in the DM than in the NM (Martyn et al 2004).…”
Section: Discussionmentioning
confidence: 89%
“…It is, however, remarkable that myostatin-null mice and cattle have a lower fat mass than the wild types (13,14). Similarly, a human child with an inactivating mutation in the myostatin gene was strikingly lean (56).…”
Section: Discussionmentioning
confidence: 99%